2013
DOI: 10.1371/journal.pone.0062831
|View full text |Cite|
|
Sign up to set email alerts
|

QTL Mapping of Flowering and Fruiting Traits in Olive

Abstract: One of the challenge fruit growers are facing is to balance between tree production and vegetative growth from year to year. To investigate the existence of genetic determinism for reproductive behaviour in olive tree, we studied an olive segregating population derived from a cross between ‘Olivière’ and ‘Arbequina’ cultivars. Our strategy was based on (i) an annual assessment of individual trees yield, and (ii) a decomposition of adult growth units at the crown periphery into quantitative variables related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 57 publications
1
34
0
Order By: Relevance
“…for total phytosterol and tocopherol contents, and for the concentrations of stigmasterol, β-sitosterol and Δ 5 -avenasterol. Broad segregation in olive progenies has been reported previously for reproductive traits (Ben Sadok et al, 2013) as well as for oil quality traits such as fatty acid profile, tocopherol content and profile, polyphenols, and carotenoids . The most interesting variation identified in the present research consisted of increased levels of Δ 5 -avenasterol (30.7% of total sterols) in the selection UC-I-2-35 and tocopherols (263.2 mg·kg −1 fruit flesh) in the selection UC-I-37-69 (Table 3).…”
Section: Discussionmentioning
confidence: 61%
“…for total phytosterol and tocopherol contents, and for the concentrations of stigmasterol, β-sitosterol and Δ 5 -avenasterol. Broad segregation in olive progenies has been reported previously for reproductive traits (Ben Sadok et al, 2013) as well as for oil quality traits such as fatty acid profile, tocopherol content and profile, polyphenols, and carotenoids . The most interesting variation identified in the present research consisted of increased levels of Δ 5 -avenasterol (30.7% of total sterols) in the selection UC-I-2-35 and tocopherols (263.2 mg·kg −1 fruit flesh) in the selection UC-I-37-69 (Table 3).…”
Section: Discussionmentioning
confidence: 61%
“…Ben Sadok et al (2013) increased the number of markers mapped on the existing Olivière 9 Arbequina map (Khadari et al 2010); the resulting female map consisted of 25 linkage groups covering 1745 cM, while the paternal map consisted of 21 linkage groups covering 1597 cM and the integrated map of 26 linkage groups covering 2148 cM. This map is currently the most saturated map obtained for olive with classic molecular markers.…”
Section: Genetic Mappingmentioning
confidence: 97%
“…Usually, the high number of characteristics useful from an agronomic or economic point of view is quantitative traits and controlled by a high number of loci (QTLs) spread in the genome. Ben Sadok et al (2013) identified 12 QTLs on the genetic map based on Olivière 9 Arbequina (Khadari et al 2010), with small effects for interesting traits such as flowering; fruiting and production at whole tree scale. The highest part of QTLs was linked to alleles from the paternal cultivar Arbequina.…”
Section: Genetic Mappingmentioning
confidence: 99%
“…Apart from some specific motives in breeding for particular tree architecture in olive, little has been done on genetics, heritability patterns and QTL mapping (Hammami et al, 2012;Moriya et al, 2012). Nevertheless, no gene related to growth pattern has been mined in olive, which reflects how much space is available for the tools of genomics (Sadok et al, 2013). Genomics and its accessory techniques are providing new dimension to the researchers for exploring the genetic and molecular processes determining the growth habit in historically related trees (Hollender and Dardick, 2015).…”
Section: ! 79mentioning
confidence: 99%